Perception Regarding Substance Abuse in Medical Students - Swati Sonawane; Rahul Peddawad; Hritika Sharma; Tanusri Tetarbe (Indian Journal of Forensic Medicine & Toxicology, 2021)
Substance abuse can become hazardous for everyone, especially the medical students as the dependency mayjeopardize their career. Substance Abuse refers to the hazardous use of psychoactive substances includingalcohol, tobacco, pain medication and illicit drugs. It torments the physical, social and emotional well-beingof an individual.Hence, we in our study will highlight the knowledge attitude and perception of medicalstudents regarding drug abuse, so that we can combat this issue diligently.Data was collected from the undergraduate medical students by using a pre-validated, self-administeredquestionnaire after taking approval from the Institutional Ethical Committee.Demographic details of the participants in our study shows that the maximum study participants belongto the age group of yrs i.e. 21-23 yrs (50%), the mean age of the study group is 20.56 yrs, with femalepreponderance of 140 (66.67%).149 participants (70.95%) believe that substance abuse has become acommon problem in medical students and according to 190 (90.48%) participants, the most affected agegroup is 18-30 years.11 (5.2%) believe that substance abuse can have potential benefits, while 84 (40%) were not sure regardingthis and the benefits stated by the study participants were euphoria.194 (92.38%) participants were aware ofthe long-term side effects of chemical dependence.The findings of the study suggest that substance abuse in an ongoing issue among medical students associatedwith deleterious consequences in various domains.